Proteomic analysis of the rare Uracoan rattlesnake Crotalus vegrandis venom: Evidence of a broad arsenal of toxins. (1st December 2015) - Viala, Vincent Louis; Hildebrand, Diana; Fucase, Tamara Mieco; Sciani, Juliana Mozer; Prezotto-Neto, José Pedro; Riedner, Maria; Sanches, Leonardo; Nishimura, Paula Juliana; Oguiura, Nancy; Pimenta, Daniel Carvalho; Schlüter, Hartmut; Betzel, Christian; et al.
Abstract: The investigation of venoms has many clinical, pharmacological, ecological and evolutionary outcomes. The Crotalus spp. venom can cause hemorrhage, neurotoxicity, myotoxicity, coagulopathy and hypotension. Although neurotoxicity and hemorrhage usually does not occur for the same species, the rare Venezuelan species Crotalus vegrandis presents both characteristic. Different from the other species it has a restricted ecological niche and geographical distribution. Nevertheless, it has a raising medical importance as this rattlesnake population is increasing. Few works describe its neurotoxic and hemorrhagic features, but other toxins might play an important role in envenomation. We combined proteomic methods to identify for the first time the main components of it venom: 2D SDS-PAGE and gel-filtration chromatography for protein mixture decomplexation; LC-MS 2 of low molecular mass fractions and tryptic peptides; bioinformatic identification of toxin families and specific protein species based on unique peptide analysis and sequence database enriched with species-specific venom gland transcripts; and finally polyclonal anti-crotamine Western-blotting. Our results point to a broad arsenal of toxins in C. vegrandis venom: PIII and PII metalloproteases, crotoxin subunits, other phospholipases, isoforms of serine proteases and lectins, l -amino-acid oxidase, nerve growth factor, as well as other less abundant toxins. Highlights: The proteome of Crotalus vegrandis venom was assessed for the first time. Unique protein species and a broad range of toxin families were identified. The translated product of a serine protease cDNA was identified in the venom.